Electrochemical study of the dissolution of oxide films grown on type 316L stainless steel in molten fluoride salt. (1st July 2021) - Qiu, Jie; Macdonald, Digby D.; Schoell, Ryan; Han, Junsoo; Mastromarino, Sara; Scully, John R.; Kaoumi, Djamel; Hosemann, Peter
Highlights: The dissolution behavior of oxide films on Type 316L stainless steel in FLiNaK salt was investigated. The oxide film formed on Type 316L SS is unstable in molten FLiNaK salt at 700 °C. The oxide dissolution rate is calculated to be 0.85 nm/h at 700 °C in molten FLiNaK salt. The O 2− in FLiNaK could react with 316L stainless steel to form FeCr2 O4 at the grain boundary of the steel. Abstract: The corrosion behavior of oxide films grown on Type 316L stainless steel (SS) in molten FLiNaK (LiF-NaF-KF: 46.5−11.5−42 mol.%) salt was investigated. The results show that the oxide film formed on Type 316L SS is unstable and can only temporarily protect materials from corrosion in molten FLiNaK salt. Based on the electrochemical impedance spectroscopy, the oxide dissolution rate is calculated to be 0.85 nm/h at 700 °C in molten FLiNaK salt. After the oxide film dissolved, Cr and Fe are selective dealloyed from the steel, leading to intergranular corrosion of Type 316L SS in molten fluoride salt.